The Potential of Prebiotic and Probiotic Supplementation During Obese Pregnancy to Improve Maternal and Offspring’s Metabolic Health and Reduce Obesity Risk—A Narrative Review - Wiedmer, Eliane B.; Herter-Aeberli, Isabelle (Frontiers in Nutrition, 2022)
Worldwide, obesity prevalence is rising, severely impairing the health of those affected by increasing their risk for developing non-communicable diseases. The pathophysiology of obesity is complex and caused by a variety of genetic and environmental factors. Recent findings suggest that obesity is partly caused by dysbiosis, an imbalanced gut microbiome. In the context of pregnancy, maternal dysbiosis increases the child’s obesity risk, causing an intergenerational cycle of obesity. Accordingly, interventions modulating the gut microbiome have the potential to interrupt this cycle. This review discusses the potential of pre- and probiotic interventions in modulating maternal obesity associated dysbiosis to limit the child’s obesity risk. The literature search resulted in four animal studies using prebiotics as well as one animal study and six human studies using probiotics. Altogether, prebiotic supplementation in animals successfully decreased the offspring’s obesity risk, while probiotic supplementation in humans failed to show positive impacts in the offspring. However, comparability between studies is limited and considering the complexity of the topic, more studies in this field are required.